ANALISIS PENGELOLAAN TERINTEGRASI UANG SEWA PADA PASAR MILIK BUMDES DALAM MENINGKATKAN PENDAPATAN KAS DESA PERSPEKTIF EKONOMI SYARIAH - Erlyana Rahayu. S; Habriyanto; Awal Habibah (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2025)
The activity of renting stalls is one of the activities that can be found in the community, especially in the market. The aim of this thesis is to find out about 1. the implementation of market rent management based on autonomy, Nevertheless, several aspects require further review, including an examination of the procedures that need to be implemented and those that have yet to be executed, such as the revenue component derived from renting market stalls Where managers need to demonstrate decisiveness in their decision-making 2. Increasing village cash income from integrated principles and 3. The impact of market rent management in increasing village cash income. The results of the research found that 1. The implementation of market rent management based on autonomy has gone well, 2. The increase in village treasury income from integrated principles has not gone well because there has been a 20% decrease in income. 3. There are several obstacles to the impact of managing market rents in increasing village cash income, namely as many as 59% of traders make payments negligently for various reasons, which continuously results in a decrease in Mentaro Island village cash income. The Sharia Economic review of the rental payments for Bumdes' Thursday Market stalls is that there are discrepancies with the initial agreement and irresponsibility (trust). Economic actors are not allowed to pursue personal gain if this harms other people.